Editorial: Community series in adaptor molecules in T cell signaling, volume II - Pongcharoen, Sutatip; Spurkland, Anne; Baldari, Cosima T. (Frontiers in Immunology, 2023)
have reported a novel signaling pathway mediated by binding of Wiskott-Aldrich syndrome protein (WASp) and diacylglycerol kinase alpha (DGK). Efficient TCR signaling is known to require inhibition of DGK triggered in response to SAP activation. The authors showed that noncatalytic region of tyrosine kinase-1 (Nck-1) and the small G protein CDC42 connect the interaction of WASp and DGK leading to the inhibition of DGK activity and T cell IL-2 response.Signaling transduction in T cells eventually leads to the NF-B transcription factor activation. This process is a critical step for T cell survival, proliferation, differentiation and function. O'Neill et al. (11) have demonstrated the existence of a signalosome containing three interacting proteins, caspase recruitment domain family member 11 (CARD11), B-cell lymphoma/leukemia 10 (BCL10), and mucosa-associated lymphoid tissue 1 (MALT1), called the CBM complex. MALT1 is known to be a scaffold for the E3 ligase tumour necrosis factor (TNF) receptor-associated factor 6 (TRAF6). The authors showed in a mouse model that the CMB is crucial for balancing T cell activation and homeostasis. In addition, Oikawa et al. ( 12) have added the new finding that this CBM complex is ubiquitinated by the E3 ubiquitin ligase called LUBAC. Using Jurkat cells in various assays and mathematical simulation, they demonstrated that LUBAC controls the activation of NF-B, critically mediating T cell functions. In addition, Hornick and Bishop ( 13) have reviewed the role of TRAF3 as a mediator of T cell differentiation and effector function. The essential function of TRAF3 has been demonstrated both in murine models and human disease caused by germline TRAF3 deficiency. The affected patients have autoimmunity, immunodeficiency, and a predisposition to B cell malignancies.Collectively, this issue contributes to provide new insights into T cell biology area involving adaptor proteins, including proximal and distal TCR signaling, thymocyte development and T cell differentiation, signalosomes relating to T cell signal transduction and regulation of cytokines and other signaling mediators. The knowledge obtained can set the foundation to novel approaches for treatment of autoimmunity and cancer.